Adsorption of Phosphate by Surface Precipitation on Lanthanum Carbonate Through In Situ Anion Substitution Reactions - Zhang, Shaoyang; Xie, Fazhi; Tang, Zhi; Zhao, Tianhui; Fang, Mengyuan; Giesy, John P. (Frontiers in Environmental Science, 2022)
Efficient removal of phosphate (PO43-) is the main solution for eutrophication. In this study, Lanthanum carbonate (La2(CO3)3) was the adsorbent of choice for the removal of PO43-. Both adsorption isotherm and thermodynamic were investigated. La2(CO3)3 was an effective adsorbent for the removal of phosphate (PO43- or H2PO4-) under weak acidic conditions (pH=2.0-6.0), the maximum adsorption amount was 106.6 mg g-1 at pH 2.9. The pHzpc of La2(CO3)3 changed from 2.1 to 6.5 prior to and after adsorption of PO43-. The mechanisms of adsorption were investigated by various techniques including Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Powder X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Based on the results obtained using XPS, during the adsorption process of PO43- by La2(CO3)3, La3+ was released and could precipitate with PO43- or H2PO4- under weak acidic conditions (pH=2.0-4.0). Adsorption was dominated by in-situ substitution reactions between CO32- and H2PO4- or HPO42-. This study provides a useful reference and potential material for the removal of PO43- in aquatic environments.